2019
DOI: 10.1186/s12864-019-6097-z
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of the four ecologically distinct cactus host populations of Drosophila mojavensis

Abstract: BackgroundRelationships between an organism and its environment can be fundamental in the understanding how populations change over time and species arise. Local ecological conditions can shape variation at multiple levels, among these are the evolutionary history and trajectories of coding genes. This study examines the rate of molecular evolution at protein-coding genes throughout the genome in response to host adaptation in the cactophilic Drosophila mojavensis. These insects are intimately associated with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 126 publications
(139 reference statements)
1
32
0
Order By: Relevance
“…Phylogenetic analysis. The phylogenetic relationship among the four D. mojavensis subspecies and D. melanogaster was determined using the recent genomic analysis of D. mojavensis (Allan and Matzkin, 2019) and the D. melanogaster FlyBase assembly (FB2019_04). The BUSCO application (Waterhouse et al, 2018) was ran using the Diptera dataset (composed of 2,799 loci) for all five genomes and a common set of 2,622 loci was obtained.…”
Section: Phylogenetic Analysis Statistics and Figure Preparationmentioning
confidence: 99%
See 3 more Smart Citations
“…Phylogenetic analysis. The phylogenetic relationship among the four D. mojavensis subspecies and D. melanogaster was determined using the recent genomic analysis of D. mojavensis (Allan and Matzkin, 2019) and the D. melanogaster FlyBase assembly (FB2019_04). The BUSCO application (Waterhouse et al, 2018) was ran using the Diptera dataset (composed of 2,799 loci) for all five genomes and a common set of 2,622 loci was obtained.…”
Section: Phylogenetic Analysis Statistics and Figure Preparationmentioning
confidence: 99%
“…Phylogenetic analyses revealed that the two northern subspecies and the two southern subspecies clustered with each other ( Figure 1B) (Allan and Matzkin, 2019). These closely-related subspecies exhibit many differences in their morphology (Pfeiler et al, 2009), neurophysiological responses (Crowley-Gall et al, 2016;Date et al, 2013;Nemeth et al, 2018), genomic and transcriptomic characteristics (Allan and Matzkin, 2019;Matzkin, 2014;Matzkin and Markow, 2013), and behavioral traits (Newby and Etges, 1998). Experimental reciprocal crosses between these allopatric subspecies resulted in viable fertile offspring, indicating presence of prezygotic isolation mechanisms (Knowles and Markow, 2001;Krebs and Markow, 1989;Markow, 1991;Zouros and Dentremont, 1980).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…These host cacti form unique chemical and nutritional environments ( Kircher 1982 ; Starmer and Phaff 1983 ), and detoxification genes in particular have seen substantial expression and coding sequence evolution across these populations ( Matzkin et al. 2006 ; Allan and Matzkin 2019 ). In addition to selection from the host, these populations experience vastly different temperature and humidity regimes, which is expected to generate selection broadly on phenology and organismal physiology ( Matzkin 2014 ).…”
Section: Introductionmentioning
confidence: 99%